Characterization and electrochemical properties analysis of reduced graphene oxide from corncob carbon as an electrode candidate: Synthesized using modified Hummers method - Eka Anggriani Odja; Raya, Indah; Maming; Muhammad Zakir; Abd. Karim; Djabal Nur Basir (Communications in Science and Technology, 2024)
This research aims to synthesize and characterize reduced graphene oxide (RGO), as well as analyse its electrochemical properties. The synthesis of RGO material from corn cobs went through several stage: carbonization, oxidation and reduction. The synthesis of RGO used a modified Hummer method, and was reduced using the reducing agent ascorbic acid. The synthesized RGO was then characterized using Fourier Transform Independent Spectroscopy (FTIR), X-Ray Diffraction (XRD), Scanning Electron Microscope (SEM), and Energy Dispersive Spectroscopy (EDS). Electrochemical analysis using the cyclic voltammetry method, the specific capacitance value obtained showed that RGO had a higher capacitance value than GO. The research results showed that carbon from corn cobs, which has not been utilized optimally, can be synthesized as a basic material for making RGO as a quite promising material.